2002
DOI: 10.1046/j.1440-0979.2002.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behaviour and burnout among staff of homes for the elderly

Abstract: This study examines relationships between experienced aggressive behaviour and burnout of staff caring for residents living in homes for the elderly (n = 551). Burnout was conceptualized as a three-dimensional syndrome consisting of emotional exhaustion, depersonalization and reduced personal accomplishment. From the results of the hierarchical regression analyses it appeared that physical and psychological aggression and the number of weekly working hours had a significant relationship with emotional exhausti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
96
0
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 29 publications
5
96
0
14
Order By: Relevance
“…The consequences are emotions like anger or anxiety extending to psychological disorders like burnout. [12,[27][28][29][30][31] Gascón et al [30] have found that there is a statistically significant association between verbal violence and anxiety and symptoms of PostTraumatic Stress Syndrome. In their report, both physical and non-physical violence has had an identical negative impact in terms of burnout, exhaustion and conflicts of values in health care workers, which are similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences are emotions like anger or anxiety extending to psychological disorders like burnout. [12,[27][28][29][30][31] Gascón et al [30] have found that there is a statistically significant association between verbal violence and anxiety and symptoms of PostTraumatic Stress Syndrome. In their report, both physical and non-physical violence has had an identical negative impact in terms of burnout, exhaustion and conflicts of values in health care workers, which are similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…
(Geriatr Nurs 2009;30:174-187) Aggressive behavior of residents continues to challenge and burden caregivers working in nursing homes [1,2]. Working in a nursing home or long-term care facility is associated with a high risk of experiencing aggression [3].Studies show that aggressive behavior is more likely to occur among older people with cognitive impairment than among those with no cognitive impairment [2,4,5] although cognitively intact residents also threaten or assault the caregivers [6].
…”
mentioning
confidence: 99%
“…Possible causes for underreporting are a lack of competence to cope with aggressive behavior, feelings of failure, or the assumption that aggressive behavior is a common feature in the care of the elderly, especially those with psychological disturbance [1,4,9,10]. Psychological disturbances and other illnesses in the elderly may lead to aggressive behavior irrespective of situational factors.…”
mentioning
confidence: 99%
“…4 This may be because the person's behaviour has passed a threshold of intolerability or is deemed unmanageable at home. In care homes these behaviours then have to be managed by care staff, [5][6][7] many of whom are poorly paid, are accorded low status and are insufficiently resourced and supported. 8,9 Behaviours can become more 'florid' (e.g.…”
Section: Definition Of Challenging Behaviour In Dementiamentioning
confidence: 99%